Clinical relevance of preformed IgG and IgM antibodies against donor endothelial progenitor cells in recipients of living donor kidney grafts - Daniel, Volker; Sadeghi, Mahmoud; Süsal, Caner; Scherer, Sabine; Tran, Hien Nicole; Gombos, Petra; Trojan, Karina; Morath, Christian; Opelz, Gerhard (Clinical transplantation, 2016)
Background Literature reports suggest that non-HLA-antibodies against human endothelial progenitor cells (EPC) can be detected in pre-transplant recipient serum and that EPC antibodies can have a deleterious influence on the graft. Methods We investigated 71 renal transplant recipients from living donors for a possible influence of pre-transplant donor-specific IgG and/or IgM recipient antibodies against EPC of the donor using the flow cytometric XM-ONE cross-match. Results Eight of the 71 patients developed acute biopsy-proven rejection. Two of these patients showed IgM antibodies against EPC prior to transplantation while the other six patients had neither IgG nor IgM EPC antibodies. Conversely, pre-transplant IgG or IgM antibodies against EPC were detected in 19 patients without acute rejection (3 × both IgG and IgM, 1 × IgG and 15 × IgM). The remaining 44 patients had neither EPC antibodies nor experienced rejection. Comparing serum creatinine levels at one month and one yr post-transplant within and among the three patient groups revealed that serum creatinine levels were similar in patients with or without EPC antibodies (p > 0.05). Conclusion In this series of 71 recipients with living donor kidneys, pre-transplant EPC antibodies detected with the XM-ONE test kit were neither associated with acute rejection nor with graft function at one month or one yr.
First published: 05 November 2015
Gesehen am 06.05.2020